Electrical and microwave absorbing properties of polypyrrole synthesized by optimum strategy. Issue 6 (31st May 2012) - Hao, Bin; Li, Liangchao; Wang, Yuping; Qian, Haisheng; Tong, Guoxiu; Chen, Haifeng; Chen, Keyu
Abstract The polypyrrole (PPy) was prepared by in situ solution polymerization. The structure and morphology were characterized by X‐ray diffractometry, scanning electron microscope (SEM), and transmission electron microscope, respectively. The electrical and dielectric properties of the PPy were measured by four‐point technique and impedance/materials analyzer. The results revealed that reaction time, reaction temperature, the types of doping agent, and the molar ratio of initiator to pyrrole monomer (nAPs/nPy) had an important effect on electrical and dielectric properties of the PPy. It showed that the PPy doped with phosphoric acid and with nAPs/nPy = 1 at 10°C for 12 h had better performance of electrical conductivity and dielectric loss. The PPy sample with 2 mm thickness had a minimum reflection loss value of −19.68 dB at approximately 16 GHz and an available bandwidth of 6.2 GHz in the range of 8–18 GHz. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013